From classrooms to real-world contexts: enhancing vaccine education through open schooling - Kwella, Hannah; Schilbert, Jana; Tessartz, Amélie; Scheersoi, Annette (Frontiers in Public Health, 2025)
The topic of vaccination has been a highly debated issue for many years, whether related to measles, HPV, or the recent COVID-19 pandemic. It necessitates deeper exploration, particularly in school biology classes where it is often superficially covered, with ethical considerations rarely addressed. To enable students to engage in an in-depth examination of this complex socio-scientific issue and to enhance their argumentation and decision-making skills, a vaccine educational project was implemented based on the concept of open schooling, where schools collaborate with various societal institutions. Over a three-day interdisciplinary program, secondary school students worked with scientists from diverse fields, including immunobiology, medicine, and ethics, across different career levels, providing varied perspectives. Students actively engaged in real-world learning contexts with authentic problems, fostering individual reflection. A qualitative study, which involved observations and interviews with students, scientists, and teachers, highlighted key success factors in developing student interest and engagement in the topic of vaccination: learner-centered design, interaction with experts, exposure to diverse professional environments, active science learning, and the integration of ethical aspects. This approach promoted not only student engagement with the complex subject matter but also critical thinking and argumentation, contributing to informed decision-making and public health awareness.